Simultaneous Imaging of Total Cerebral Hemoglobin Concentration, Oxygenation, and Blood Flow During Functional Activation - Preecha P Yupapin (My University, 2013)
Magnetic therapy is an alternative medicine practice involving the use of magnetic fields subjected to certain parts of the body and stimulates healing from a range of health problems.In this paper, an embedded nano antenna system using the optical spins generated from a particular configuration of micro rings (PANDA) is proposed.Magnetic moments could indeed arise from the intrinsic property of spins (optical spins).By controlling some important parameters of the system such as soliton input power, coupling coefficients and sizes of rings, output signals from micro ring resonator system can be tuned and optimized to be used as magnetic therapy array.
Keywords: Blood oxygenation; Molecular Communication and Nanonetworks